Relevansi Keteladanan Guru dalam Pembentukan Karakter Siswa yang Religius - Rohani, Aryawan Efendi; Sileuw, Marwan; Iribaram, Suparto (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2023)
As an educator, the teacher’s attitude and behavior are often played as role models for students. Unfortunately, there were few studies discussed this context and only focus on the process of object-based values formation, so that the teacher's qualifications as a subject tend to be neglected in scientific discussions. This study focuses on